Struktur Relasi Kekuasaan Dan Komunikasi Elit Desa Dalam Implementasi Program Koperasi Desa Merah Putih - Yorry Hardayani (STAI Bumi Silampari, 2026)
This study analyzes the structure of power relations and communication patterns among village elites in the implementation of the Merah Putih Village Cooperative Program in Bioa Sengok Village, Lebong District, Bengkulu. Using a qualitative approach with data triangulation through in-depth interviews, participant observation, and focus group discussions, the study identified three categories of village elites: formal elites (village officials), informal elites (traditional/religious leaders), and economic elites (local entrepreneurs). The findings show the dominance of informal elites in social legitimacy through strong social and symbolic capital, while formal elites have limited technical knowledge despite their legal authority. The implementation of the program faces challenges in coordination between elites, unclear regulations, and potential overlap with existing BUMDes (village-owned enterprises). The results of the study confirm the gap between top-down program design and the reality of local power. Self-help cooperatives based on social law proved to be more effective than formal programs, demonstrating the importance of traditional legitimacy and social control mechanisms in village governance. The study concludes that optimizing the implementation of the Merah Putih Village Cooperative Program requires reconfiguring power relations to be more equitable by strengthening the capacity of formal elites, revitalizing the role of informal elites, developing checks and balances mechanisms, and strengthening a clear regulatory basis to prevent elite capture and provide a more equitable distribution of benefits for village communities.